The magic school bus on the ocean floor - Cole, Joanna; Degen, Bruce (New York : Scholastic, 1992)
On another special field trip on the magic school bus, Ms. Frizzle's class learns about the ocean and the different creatures that live there.
Keywords: Marine animals -- Juvenile literature; Ocean bottom -- Juvenile literature; Ocean; Marine animals